Transcriptomics and Other Omics Approaches to Investigate Effects of Xenobiotics on the Placenta - Rosenfeld, Cheryl S. (Frontiers in Cell and Developmental Biology, 2021)
The conceptus is most vulnerable to developmental perturbation during its early stages when the events that create functional organ systems are being launched. As the placenta is in direct contact with maternal tissues, it readily encounters any xenobiotics in her bloodstream. Besides serving as a conduit for solutes and waste, the placenta possesses a tightly regulated endocrine system that is, of itself, vulnerable to pharmaceutical agents, endocrine disrupting chemicals (EDCs), and other environmental toxicants. To determine whether extrinsic factors affect placental function, transcriptomics and other omics have become more widely used. In casting a wide net with such approaches, they have provided mechanistic insights into placental physiological and pathological responses and how placental responses may impact the fetus, especially the developing brain through the placenta-brain axis. This review will discuss how such omics technologies have been used to understand the effects of EDCs, including the widely prevalent plasticizers bisphenol A (BPA), bisphenol S (BPS), and phthalates, other environmental toxicants, pharmaceutical agents, maternal smoking, and air pollution on placental gene expression, DNA methylation, and metabolomic profiles. It is also increasingly becoming clear that miRNA (miR) are important epigenetic regulators of placental function. Thus, the evidence to date that xenobiotics affect placental miR expression patterns will also be explored. Such omics approaches with mouse and human placenta will assuredly provide key biomarkers that may be used as barometers of exposure and can be targeted by early mitigation approaches to prevent later diseases, in particular neurobehavioral disorders, originating due to placental dysfunction.